The impact of local environmental differences on the phenotypic plasticity and genetic variation of Kazakhstani populations of Paeonia anomala - Turzhanova, Ainur S.; Kubentayev, Serik A.; Magzumova, Saule M.; Sarkytbayeva, Aisulu K.; Khapilina, Oxana N. (Frontiers in Ecology and Evolution, 2025)
Medicinal plants are highly vulnerable to overexploitation and environmental pressures, leading to a risk of extinction. Local ecological heterogeneity influences phenotypic variability and adaptive responses to stress. Species survival under specific conditions depends on genome plasticity, which can be altered by the activation of retrotransposons that are sensitive to environmental changes. Genome profiling using the inter-primer binding site (iPBS) polymerase chain reaction (PCR) method enables the assessment of genetic polymorphisms within and between populations over small geographical ranges, thereby providing crucial insights for conservation efforts. Paeonia anomala L. (P. anomala) is a valuable medicinal plant that has experienced a population decline in Kazakhstan due to extensive harvesting for medicinal use. This study investigated and analyzed the morphometric traits, genetic diversity, and environmental conditions of five P. anomala populations in the Kazakh Altai. Phenotypic variability analysis revealed significant interpopulation differences in traits such as plant diameter, plant height, raw biomass, and leaf blade length and width. We found that spatial orientation, slope angle, and human activity had a significant effect on the phenotypic variability of P. anomala plants in the studied populations. Genetic analysis using iPBS genome profiling identified 1,176 PCR fragments, of which 860 were polymorphic, with polymorphism levels ranging from 46% to 64%. The IVA population exhibited the highest genetic variability (He = 0.212; I = 0.315), whereas the ASU population exhibited the lowest genetic diversity (He = 0.163; I = 0.244). Our study provides a better understanding of P. anomala population differentiation under local environmental conditions and supports the development of effective conservation strategies.